Perbandingan busi standar dan busi multi elektroda terhadap kinerja dan emisi gas buang pada mesin bensin - Sebayang, A. H.; Ibrahim, H.; Sutrisno, J.; Nurulita, B. (Dinamika Teknik Mesin: Jurnal Keilmuan dan Terapan Teknik Mesin, 2020)
Spark ignition in internal combustion engine was occurred from the spark of the electrode which is in the middle of the spark plug. The purpose of this study was to analyze the engine performance and exhaust emissions of a gasoline engine using standard spark plugs and multi-ground electrode spark plugs. Tests are carried out on four-stroke and four-cylinder gasoline engines without engine modification at 1500 to 4000 rpm. In addition, engine torque, brake specific fuel consumption and brake thermal efficiency and carbon monoxide (CO), carbon dioxide (CO2) and hydrocarbon (HC) emissions are measured. From the results of the study, an increase in torque and power using a four-foot electrode spark plug by 0.599% was accompanied by an increase in the consumption of specific fuels 266.78 g/kWh compared to standard spark plugs. In addition, it was found that CO and HC emissions decreased, although CO2 emissions increased compared to the use of standard spark plugs. Based on the results of the study, it can be concluded that the use of multi-ground electrode spark plugs can increase engine power and torque and reduce exhaust emissions.